The Essence of Competitive Strategy - Bowman Cliff; Faulkner David (Prentice Hall, 1995)
This book explains the answers by providing a unique framework for developing viable competitive strategies. Introduction, The Customer Matrix, The Producer Matrix, The Competitive Environment, The Future, Strategic Choice, Joint Development and Acquisition, Implementation Through Internal Development, Conclusion, References, Index.